Cultural Misrepresentations of the COVID-19 Response in Indonesia - Zainal, Asliah; Rezki, Anita; binti Awad, Faizah; Ainul Rafiah, Waode (KnE Social Sciences, 2022)
The cultural aspects of Indonesian society have been overlooked by government policies aimed at preventing the spread of COVID-19. The Government has tended to overlook Indonesian society’s visible and intimate culture, whether on a daily basis or in the face of unforeseen events such as crises. The data for this study were gathered by tracking COVID-19-related news on the internet, narrative and message content on social media, and television broadcasts. The absence, as well as the neglect, of local wisdom and local perspectives in preventing the spread of COVID-19 in Indonesia were mapped using primary data and critical analysis. The findings revealed that cultural misrepresentations in the handling of COVID-19 manifested themselves in a variety of ways, including the Government’s sole authority, the use of foreign languages, instructional messages, and community traditions. The neglect of culture has aided the virus’s spread, and society’s response has been indifferent, if not chaotic. This paper argues that if the lack of culture in the handling of COVID-19 is allowed to continue, the government-society relationship will become more distant, not only in terms of social but also cultural distancing. Keywords: COVID-19, pandemic, media online, media social, social distancing, cultural distancing